Compensation for land for the construction of the Medan-Tebing Tinggi toll road in 2013 - Aisyah, Aisyah; Giawa, Apelin; Syafruddin, Syafruddin; Afrita, Afrita; Sidabariba, Burhan (Lafadz Jaya Publisher, 2023)
Road Infrastructure Development Projects not only serve to facilitate and accelerate access to communities everywhere but also as a means to stimulate economic growth and tourism in a region. In the process of liberation of rights, landowners must be given a sense of justice and legal certainty in paying losses fairly and in accordance with the procedures regulated by law. For that I raised the title of the research “Compensation of Land Construction Road Tol Medan-Tebing High Year 2013” to understand the legal protection that Pemkot has in acquiring land and the mechanism of solving the problem of land acquisition. The types of research used are normative juridic and qualitative descriptive. Techniques of data collection through interviews and observations and libraries. The data is collected and analyzed qualitatively. According to paragraph 2, no. 2 In 2012, the legal protection in land acquisition for the public interest includes the provision of fair and fair compensation to the legal party. Articles 17 and 18 of Kepres No. 36 of 2005 regulate the determination of damages. In accordance with the Law No. 2 of 2012, the process of procurement of highway tolls Field-Tebing began.